Intra-assemblage variation in the macro-blade assemblage from the 1963 excavation at Shuidonggou locality 1, northern China, in the context of regional variation - Li, Feng; Kuhn, Steven L.; Chen, Fu-you; Gao, Xing (PLOS ONE, 2020)
The emergence of the Upper Paleolithic and regional variability in early Upper Paleolithic industries are prominent topics in Paleolithic archaeology, with special relevance to the dispersal and differentiation of early modern human cultures across Eurasia. The so-called Initial Upper Paleolithic (IUP) has been considered a key element in the emergence of the Upper Paleolithic in northern Asia. Here, we examine the intra-assemblage variation in the collection from the 1963 excavation at Shuidonggou locality 1, a major IUP site in northern China. We combine technological and quantitative attribute analyses to investigate the variety of core reduction sequences and tool manufacture behaviors at the site. A range of core reduction sequences have been documented at Shuidonggou locality 1, including both simple core reduction and prepared core reduction yielding laminar (blade-like) products. The simple core reduction component may due to mixed non-IUP assemblages from different archaeological layers. Among the laminar core reduction sequences, the main strategy involves asymmetrical exploitation of the broad face of core blank, producing blades and elongate flakes, and resembling a recurrent Levallois blade method sensu lato. We compare Shuidonggou laminar blank production with that of IUP assemblages in the Siberian Altai, northern Mongolia, and the Transbaikal region. The comparison demonstrates a general consistency to the basic blank production in IUP assemblages across northern Asia, with some regional variation. The results suggest a multi-directional model of diffusion of the IUP in northeast Asia.